Entrepreneurial Knowledge and Entrepreneurial Orientation on Enterprises Performance: a Study of Smes in East Java, Indonesia - Isna Nur Rahmawati; Adi Santoso; Riawan Riawan (Ekonomis: Journal of Economics and Business, 2023)
The research aims to examine and analyze the effect of Entrepreneurial Knowledge, Market Orientation, Sales Orientation, and Networking on Enterprises Performance. The population of this research is SMEs in East Java. The number of samples for this study is 300 SMEs. The research sample collection method uses non – probability sampling. This study uses primary data obtained by distributing questionnaires online using Google Forms. The data collection method uses a questionnaire distributed via Google Forms. Data measurement uses a linear scale of 1 to 4 where 1 is for strongly disagree and 4 is for strongly agree on answers. Data processing uses the SmartPLS 3 application. The results of this study found that Entrepreneurial Knowledge, Market Orientation, Sales Orientation, and Networking influence Entrepreneurial Knowledge and Entrepreneurial Orientation have a positive and significant effect on enterprises performance; Study on SMEs in East Java, Indonesia. This can be seen from the results of the discriminant validity test and the final result of SmartPLS 3 data processing.